Interpretasi Ayat-Ayat Taḥżīr dalam Tafsir Ibnu ʻĀsyūr dan Relevansinya terhadap Pembentukan Karakter Pelajar - Iskandar, Zeindri Riyan; Zein, Achyar; Nasution, Muhammad Ali Azmi (Jayapangus Press, 2025)
The taḥżīr verses in the Quran are moral-spiritual warnings addressed to humans to avoid reprehensible behavior and its negative impacts. However, in the context of modern education, these warnings have not been fully internalized by students, so that moral degradation, such as intolerance, hedonistic behavior, and weak academic ethics, is still often found. This study aims to analyze the interpretation of the taḥżīr verses in Ibn ʻĀsyūr's al-Taḥrīr wa al-Tanwīr and explore their relevance for the formation of student character. The research method employs a qualitative approach, utilizing a literature study model, where primary data are derived from Ibn ʻĀsyūr's Tafsir, and secondary data are sourced from thematic tafsir literature, character education, and contemporary studies on student ethics. The results of the study indicate that the taḥżīr verses, according to Ibn ʻĀsyūr, are not only textual prohibitions, but also contain pedagogical dimensions that emphasize aspects of rationality, moral awareness, and social responsibility. The novelty of this study lies in its contribution to the thematic exegesis, specifically by highlighting the function of the taḥżīr verses not only as normative warnings but also as applicable moral education instruments for the younger generation. By interpreting taḥżīr as a preventive tool that forms spiritual, social, and intellectual vigilance, this study broadens the understanding that tafsir does not merely explain the meaning of verses but also offers a conceptual framework for strengthening character education. Its relevance is seen in the integration of the values ​​of honesty, discipline, responsibility, critical thinking, and social concern in educational practices, so that this study makes a real contribution in addressing the moral crisis of the younger generation while enriching the perspective of tafsir as a foundation for Islamic character education that is adaptive to the challenges of the times.